2012
DOI: 10.1021/pr300188b
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Workflows Optimized for In-gel, In-solution, and On-filter Proteolysis in the Analysis of Plasma Membrane Proteins

Abstract: Proteomic studies of plasma membrane proteins are challenged by the limited solubility of these proteins and the limited activity of proteolytic enzymes in solubilizing agents such as SDS. In this work, we have evaluated three bottom-up workflows to obtain tryptic peptides from plasma membrane proteins solubilized with 2% SDS. The workflows are: in-gel digestion, in-solution digestion, and on-filter digestion. The efficiencies of these strategies, optimized to employ different matrices for trypsin cleavage, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(79 citation statements)
references
References 20 publications
2
72
0
Order By: Relevance
“…FASP and in-gel-digestion resulted in much lower peptide recoveries than SOD or in-solution-digestion (p < 0.05); this problem is more pronounced when the level of the target mAb was low (e.g., 1 μg/mL, Figure 3A), which can be attributed to the peptide loss due to the absorption of peptides in the gel or filter. 17,40 In terms of the variation of the peptide recovery, the rank is in-geldigestion > FASP > SOD ≈ in-solution-digestion. The relatively large variations by in-gel-digestion and FASP likely root from the absorption of peptides on the gel/filters.…”
Section: Analytical Chemistrymentioning
confidence: 99%
“…FASP and in-gel-digestion resulted in much lower peptide recoveries than SOD or in-solution-digestion (p < 0.05); this problem is more pronounced when the level of the target mAb was low (e.g., 1 μg/mL, Figure 3A), which can be attributed to the peptide loss due to the absorption of peptides in the gel or filter. 17,40 In terms of the variation of the peptide recovery, the rank is in-geldigestion > FASP > SOD ≈ in-solution-digestion. The relatively large variations by in-gel-digestion and FASP likely root from the absorption of peptides on the gel/filters.…”
Section: Analytical Chemistrymentioning
confidence: 99%
“…We have undertaken to enrich the entire plasma membrane to analyze integral proteins and proteins from both the inner and outer surfaces, using pellicles formed with cationic nanoparticles. We are also optimizing a proteomic workflow to provide proteolysis of highly hydrophobic proteins (8). …”
Section: Introductionmentioning
confidence: 99%
“…Due to absence of bovine urinary proteome database, results of this study were compared with the human urinary proteome prepared by AS: proteins precipitated by ammonium suphate precipitation; PS: proteins extracted by ProteoSpin column urine concentration kit and DF: diafiltered samples were directly used for proteome analysis without any precipitation. compiling three extensively studied databases representing a total of 3395 proteins [7,16,25]. Of these proteins, 315 proteins (Supplementary Table 5) identified in this study overlapped with human urinary protein database significantly expand the number of proteins (n = 1256) identified in bovine urine as shown in Fig.…”
Section: Comparison With Other Urinary Proteome Datasetsmentioning
confidence: 68%
“…In addition, the resolution of the extracted proteins was very poor. Specifically, it was difficult to re-solubilize the protein pellet obtained from acetone and methanol precipitation as reported earlier [25,26]. It has been reported that acetone precipitates some salts and other metabolic waste components along with proteins [26] resulting in poor quality 2DE.…”
Section: Assessment Of the Quality Of Extracted Proteins For Lc-ms/msmentioning
confidence: 95%
See 1 more Smart Citation